Pandemic's Impact on the Students of Office Administration's Shorthand Proficiency - Mapusao, Jayson R.; Jugueta, Roshel A.; Bingo, Mariel C.; Ramirez, Crisanto S. (The Indonesian Institute of Science and Technology Research, 2023)
This study was conducted to determine the Pandemic's impact on the students of Office Administration's shorthand proficiency at Camarines Norte State College (CNSC). Data were gathered through a survey questionnaire with a 5-point Likert scale using the descriptive method. Percentage and weighted mean were the statistical tools used to interpret the results. Ninety-five (95) 2nd year and 3rd-year students served as respondents through total population sampling. The results revealed that students are moderately proficient in shorthand writing and ineffective in time management, while rather proficient in shorthand reading and lack of reading materials was the factor. Lastly, proficiency in English grammar and communicating/interacting in a class discussion was the factor. Based on the results, an action plan was formulated as a recommendation, which includes providing innovative devices such as iPads or tablets to facilitate online stenography instruction and study.